(untitled) (Itinera, 2024)
The paper addresses the exploration of women’s nature, intended as a peculiar conditio muliebris, focussing on woman artists that reflected on the female body with Postmodernist artistic means. Starting with an analysis of the theoretical propositions of Art Feminism practitioners such as Lucy Lippard, Valie Export, and Mary Kelly, who highlight the alterity of female nature and, thus, of woman’s art, the paper later discusses three art installations addressing bodily explorations by woman artists belonging to different generations: Mary Kelly’s Post-Partum Document (1973- 79), Mona Hatoum’s Corps étrangers (1994), and Sondra Perry’s Wet and Wavy Looks—Typhon coming on (2016). The paper argues that these installations substantiate the mentioned theoretical propositions and form a thread of bodily awareness that allows woman artists and the wider public to ascertain female nature by means of a fully aesthetic mimesis. The relationship between art and nature thus becomes one of mimetic exploration of the female body that leads to the acknowledgment of a gender-specific corporal feeling.